Analysis of Escherichia coli and Total Plate Count of Red Guava Fruit Juice (Psidium guajava L.) Sold in Keboansikep Gedangan Subdistrict Sidoarjo - Hafis Reonanda; Kurnia Hartati, Fadjar; Nunuk Hariyani; Bambang Sigit S. (Demeter: Journal of Farming and Agriculture, 2023)
Red guava can be processed into a juice drink, but it does not rule out the possibility that fruit juice contains disease-causing microorganisms. This study aims to determine the number of Escherichia coli and TPC/Total Plate Count bacteria in red guava fruit juice sold in the Keboansikep, Gedangan, Sidoarjo. The method used is descriptive using a survey technique with a cross-sectional approach. Laboratory experiments are carried out, namely analyzed in the microbiology laboratory sampling using a saturated sampling technique. Samples were examined to compare the analysis results obtained compared to INS 3719:2014 concerning the Quality of Fruit Juice Drinks. Samples were examined using Escherichia coli analysis based on INS 01-2332.1-2006 with the Most Probable Number (MPN) method and Total Plate Count/TPC analysis based on INS 01- 2332.3-2006 with the pour plate method. The test results showed that the Escherichia coli analysis obtained 100% of the samples showing positive with the lowest MPN index of 9 APM/ml to the highest >1100 APM/ml. The results of the PNA analysis obtained 7% of all samples, indicating that it was safe and met the requirements, namely sample 7A with a TPC value of 4.9 x 103 CFU/ml, while 93% of all samples showed that it was unsafe or did not meet the requirements based on INS 3719: 2014. The sample containing the most microbes was sample 5A with a TPC value of 5,1 x 105 CFU/ml